Middle voice in modern Greek : meaning and function of an inflectional category - Manney, Linda Joyce (Studies in language companion series, 2000)
This book provides an in-depth analysis of the inflectional middle category in Modern Greek. Against the theoretical backdrop of cognitive linguistics, it is argued that a wide range of seemingly disparate middle structures in Modern Greek comprise a complex semantic network, and that this network is organized around two prototypical middle event types, which are noninitiative emotional response and spontaneous change of state. In those cases where middle structures have active counterparts, middle and active variants of the same verb stem are compared in order to demonstrate more clearly the.